TRANSLATING FROM LITHUANIAN INTO ITALIAN: FIVE YEARS AFTER TURIN 2007 - Cerri, Adriano (Vertimo studijos, 2017)
This review deals with the most recent translations from Lithuanian into Italian. It is intended as a sequel to previous works (e.g. Dini 2007b; Dini, Klioštoraitytė 2009). The focus is the years 2008–2012. All the translations which appeared in this period are reviewed with two objectives in mind: a) to update the data; b) to analyse the situation after the 2007 Turin Book Fair, where Lithuania was the guest of honour. The analysis suggests both negative and positive conclusions. Compared to the period 2005–2008, there was a drop in the number of translations. This may have been a natural effect after the rapid growth due to the Fair; however, the drop in translations can be largely attributed to the economic crisis. In fact, the 2011 Bologna Children’s Book Fair did not cause the same surge in the market of translation. Regrettably, some translators who worked in the pre-Turin years have not continued; thus, the small number of translators is currently a problem. On the other hand, there are also positive signs. Several important and highquality translations have appeared recently. The efforts of the few main translators have even increased over the years and, finally, some new translators and new publishing companies are slowly emerging.